DESIGN AND ANALYSIS OF INERTIA VIBRATOR WITH ADJUSTABLE ECCENTRIC MASS - DUAN XinHao; QU PengZhe; LIU WeiXiang; ZHANG ChunHua; TAO Ying; LI PengYu (Jixie qiangdu)
In order to make the exciting force adjustment of inertia vibrator during operation possible,and to meet the demand of particular vibrating machines,a kind of inertia vibrator is designed,it’s eccentric mass can be adjusted by pressure air. The design principal,structure design,analysis and calculation model is established. Furthermore,the relationship of centrifugal force to rotating speed,pressure,as well as the both,and the equations and curves are drawn and established. The research results could be guidance for design and production of institutes and factories.